2013
DOI: 10.1093/aje/kws583
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Pelvic Inflammatory Disease Following Chlamydia trachomatis Infection: Analysis of Prospective Studies With a Multistate Model

Abstract: Our objective in this study was to estimate the probability that a Chlamydia trachomatis (CT) infection will cause an episode of clinical pelvic inflammatory disease (PID) and the reduction in such episodes among women with CT that could be achieved by annual screening. We reappraised evidence from randomized controlled trials of screening and controlled observational studies that followed untreated CT-infected and -uninfected women to measure the development of PID. Data from these studies were synthesized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 53 publications
2
105
0
2
Order By: Relevance
“…Chlamydia Trachomatis (CT) is a common sexually transmitted infection of young people which if left untreated will cause pelvic inflammatory disease (PID) in around 16% of women (1). PID may then result in adverse reproductive outcomes such as ectopic pregnancy (EP) or tubal factor infertility (TFI) (2).…”
mentioning
confidence: 99%
“…Chlamydia Trachomatis (CT) is a common sexually transmitted infection of young people which if left untreated will cause pelvic inflammatory disease (PID) in around 16% of women (1). PID may then result in adverse reproductive outcomes such as ectopic pregnancy (EP) or tubal factor infertility (TFI) (2).…”
mentioning
confidence: 99%
“…Mathematical modeling suggested that PID can occur at any time point during the natural history of an infection; therefore, annual chlamydial screening programs may reduce the incidence of PID (14). A separate model concluded that annual screening could prevent 61% (95% credible interval, 55 to 67%) of Chlamydiaassociated PID (15).…”
mentioning
confidence: 99%
“…Annual screening would prevent 61% of Chlamydia-related pelvic inflammatory disease in women who became infected. 4 Primary care providers are in a unique position to screen patients for risky behaviors and prevent associated morbidity and mortality.…”
mentioning
confidence: 99%